2005
DOI: 10.2320/matertrans.46.1958
|View full text |Cite
|
Sign up to set email alerts
|

Stress Relaxation of Poly-Si Film Formed by Excimer Laser Annealing

Abstract: We investigated the low-temperature processed polycrystalline-silicon (poly-Si) film formed by carrying out low-energy-density and multishot excimer laser annealing (ELA) of amorphous Si (a-Si) film on a glass or quartz substrate. The influence of secondary grain growth which grain size becomes larger than the film thickness on the tensile stress relaxation of the poly-Si film was clarified. Relationship between hydrogens which are supplied to the melt-Si from the bottom catalytic-chemical vapor deposition (Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…In this case, high-quality poly-Si films must be prepared at low temperatures below 200 C. The poly-Si films prepared by the crystallization of amorphous silicon (a-Si) using excimer laser annealing (ELA) have been examined. [1][2][3][4] It is known that hydrogen (H) in a-Si film causes film exfoliation. Therefore, the H concentration is decreased to below 1 at.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, high-quality poly-Si films must be prepared at low temperatures below 200 C. The poly-Si films prepared by the crystallization of amorphous silicon (a-Si) using excimer laser annealing (ELA) have been examined. [1][2][3][4] It is known that hydrogen (H) in a-Si film causes film exfoliation. Therefore, the H concentration is decreased to below 1 at.…”
Section: Introductionmentioning
confidence: 99%
“…Grain size and crystallinity of poly Si have traditionally been characterized by X-ray diffraction (XRD), high resolution scanning electron microscopy (HRSEM) and crosssectional transmission electron microscopy (XTEM) (6)(7)(8)(9)(10). XRD does not have high spatial resolution and only gives average grain size over large measurement areas.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that grain growth toward the lateral direction was prevented by H in a-Si films with a uniform and high H concentration or high energy irradiation. 14) On the other hand, the projection size of the poly-Si films related to the grain size 15) increase occurring with an increase in shot number for ELHMD. The theory of secondary grain growth in the solid phase was studied by Thompson.…”
mentioning
confidence: 99%